Disease-associated immune cell endotypes in anti-MDA5-positive dermatomyositis using unbiased hierarchical clustering - Guo, Ruru; Yang, Yang; Gu, Liyang; Li, Xinyu; Ma, Yiyangzi; Liu, Xuesong; Lu, Liangjing (Frontiers in Immunology, 2024)
Objective Clinical and prognostic features of Anti-MDA5-Positive Dermatomyositis (MDA5+ DM) are diverse. This study aimed to examine the peripheral immune cell profiles of patients with MDA5+ DM, identify disease endotypes related to the heterogeneous manifestations and prognosis, and guide individualized therapy regimen. Methods This inpatient cohort included 123 patients with MDA5+ DM. Unsupervised hierarchical clustering analysis was used to derive disease endotypes from the circulating immune cell profiles on admission. Clinical symptoms, laboratory test results, inpatient treatments, and disease outcomes were then analyzed among the identified endotypes.Results Three disease endotypes in MDA5+ DM were identified from peripheral immune cell profiles. Endotype1 had the highest percentages of CD4 + T cells and monocytes, and the lowest percentage of neutrophils; Endotype2 had the highest percentage of B cells; Endotype3 had the highest percentage of CD8 + T cells and NK cells. Clinical and prognostic heterogeneity of the endotypes were revealed. Endotype1 had the lowest 3-month mortality with the high incidence of periungual capillary changes. Endotype2 and Endotype3 had higher prevalence of rapidly progressive interstitial lung disease (RPILD) and mortality at 3 months than Endotype1. Meanwhile, Endotype3 had higher pneumocystis jiroveci and CMV viremia cases with significantly elevated of activated CD8 + T cells and multiple cytokines than Endotype1.2 Conclusion Clustering analysis of peripheral immune cell profiles identified three different endotypes in MDA5+ dermatomyositis. Endotpye2 and 3 showed higher RPILD, 3-month mortality, pneumocystis jiroveci and CMV viremia.